Foundation for Integrating Employee Health Activities for Active Duty Personnel in the Department of Defense - Cecchine, Gary (RAND Corporation, 2009)
The authors describe current Department of Defense safety and occupational health programs and health information systems, as well as employee health programs outside of DoD to provide a foundation for considering a more integrated Department of Defense employee health program.